Spread the News, the Future Looks Bright for Prosthodontics - Stephen F. Rosenstiel, BDS, MSD,1 Daniel H. Ward, DDS,2 and (Blackwell Synergy, 2000)
This study aimed to determine dentists’ esthetic preferences of the maxillary anterior teeth as influenced by different proportions. The goal was to link choices to demographic data as to the experience, gender, and training of the dentist.